DEVELOPING SPEAKING SKILLS AND USING INTERACTIVE ACTIVITIES. (Conference Zone, 2022)
this article reveals the role of interactive activities in the teaching of a foreign language. The author of the article believes that the importance of learning a foreign language is undisputed. But there are a lot of problems in the process of learning a foreign language